Community voices on climate, peace, and security: Mindanao, Philippines - Medina, Leonardo; Savelli, Adam; Souza de Matos, Vanessa; Kizilkaya, Setenay; Torres, Mark Anthony; Arcede, Jayrold; Jaquet, Stéphanie; Sabugaa, Michael; Hellin, Jon; Sieber, Stefan; Bonatti, Michelle; Pacillo, Grazia (2024)
This Community Voices on Climate, Peace and Security series report presents the results of a participatory appraisal conducted with residents of three localities across Mindanao, Philippines. Based on the qualitative analysis of data gathered through focus group discussions with community members in each location, we identified four causal pathways through which the effects of climate change undermine institutional and community capacities for sustainable peacebuilding in Mindanao’s post-conflict setting. Under a context of intense armed conflicts and localized feuds, often rooted in historical grievances and political exclusion, these impacts, coupled with an uneven distribution of benefits from resilience initiatives, erode the adaptive capacities of communities and heighten anti-state sentiments. The ramifications extend beyond environmental concerns to profoundly affect livelihoods and exacerbate existing tensions, amplifying the complexity of resilience-building efforts. This report also co-developed entry points for environmental management and climate adaptation to support policy efforts for sustainable peacebuilding. Study participants designed actionable proposals which mostly rely on their own collective action but require support from surrounding policy systems and the international community for their implementation.